Ponešto o nacionalizmu i ekstremizmu/ Something about Nationalism and Extremism - Fočo, Adnan (Pregled: časopis za društvena pitanja / Periodical for social issues, 2024)
In the paper I try to shed light on the issue of extremism and its forms that are realized in social reality, especially in the area of Bosnia and Herzegovina. In the paper, I try to show not only the terminological meaning of nationalism and extremism, but also its reflection on the social environment. In the political reality and social environment in which extremism has become a model or value system, collective homogenization and manipulation of the mass or ethnos occurs. National parties strive, through national extremism, to realize their political goals and present themselves as representatives and protectors of national or ethnic and national interests. In this extremist vortex, we will try to indicate the means by which extreme ideas are realized, which are primarily the media, religious structures and young people as the most suitable form of extreme practical political action.